Impact assessment of apartment building foundation to Terban spring discharge, Yogyakarta City - Wahyu Wilopo; Doni Prakasa Eka Putra; H Setiawan; K D Setyawan (Journal of Degraded and Mining Lands Management, 2020)
The development growth of hotel and apartment in Yogyakarta city is considered to have an impact on groundwater, especially springs located along the river across Yogyakarta city. Most of the foundations of hotels and apartments are below the groundwater level. Therefore, this study aimed to predict the impact of apartment building foundations on Terban spring discharge in Yogyakarta city. Method of impact prediction was conducted by groundwater modeling approach before and after the apartment is built. Visual Modflow 3.1 software was used to develop groundwater modeling in the research area with input parameters including rock types and layers, permeability value of each rock, recharge, model boundary, groundwater level and apartment foundation design. The simulation results show that the impact of apartment foundations on the Terban spring water discharge causing decreased by 4.12% or 0.027 litres/second. Although the amount of spring discharge is relatively small, therefore it is necessary for groundwater conservation to keep the spring discharge stable by developing recharge wells.